The relevance of the ternak uang financial strategy to the principles of maqāṣid al-sharī‘ah and al-ghazali’s ethics of wealth - Fanani, Ahmad Farid; Annuha, Ahmad Nabil; Pratama, Muhammad Yusuf (Faculty of Islamic Economics and Business UIN Salatiga, 2025)
Timothy Ronald’s Tangga Ternak Uang has gained widespread attention among young Indonesian Muslims as a practical and accessible step-by-step financial guide. This study aims to examine how Islamic principles are reflected in each of the strategy’s seven stages through the lens of maqāṣid al-sharī‘ah and Al-Ghazali’s thought. Using a qualitative method, this research draws upon content analysis of video materials and relevant classical and contemporary literature. The findings show that every stage from saving and debt repayment to long-term investment and philanthropy embodies the value of wealth protection (ḥifẓ al-māl), moral responsibility, and barakah-oriented behavior. The strategy resonates with Al-Ghazali’s emphasis on spiritual ethics, risk anticipation, and wealth as a means for societal welfare. Nonetheless, the model has yet to be empirically tested in the context of user behavior or socio-economic impact. This study contributes to the development of Islamic financial literacy models rooted in maqāṣid-based ethical frameworks.